Ketahanan Industri Halal, Fluktuasi Variabel Ekonomi Makro Islam, dan Konsumsi Selama Ramadan di Indonesia - Hidayat, Muhammad Syahrul; Rohmah, Rika Rizki; Fauziah, Nur Mahmudah Apriliah; Margareta, Andini Ardy; Fauziah, Atiqo Mita (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This study examines the resilience of the halal industry in Indonesia against fluctuations in Islamic macroeconomic variables and consumption patterns during Ramadan using a quantitative approach based on the Error Correction Model (ECM). Secondary data were obtained from Statistics Indonesia (BPS), Bank Indonesia, the Financial Services Authority (OJK), the National Committee for Islamic Economy and Finance (KNEKS), and the Indonesia Stock Exchange (IDX) over a ten-year period (2015–2024). The data were collected quarterly, resulting in 40 observations. The estimation results indicate that in the short term, the Halal Industry Resilience Index, Indonesia Sharia Stock Price Index, Rupiah exchange rate against the gold dinar, Zakat, Infaq, and Sadaqah (ZIS), Halal Food Price Index, and changes in demand for halal products during Ramadan positively contribute to the resilience of the halal industry. In contrast, the Sharia Financial Index and household consumption expenditure in the halal sector have a negative impact due to the shift of funds toward the Islamic financial sector andconsumption that is not matched by production. In the long term, exchange rate stability, the distribution of ZIS, and the growth of Islamic stocks are the key factors in maintaining the resilience of the halal industry. These findings align with the halal supply chain theory and Islamic economics, which emphasize economic justice and sustainability. Therefore, optimizing the distribution of Islamic social funds, enhancing supply chain efficiency, and promoting innovation and digitalization are necessary to improve the competitiveness of Indonesia’s halal industry. This study is the first to introduce and empirically examine both the short-term and long-term effects of variables that have not previously been tested together in the context of halal industry resilience.